Transnational and Local Co-ethnic Social Ties as Coping Mechanisms Against Perceived Discrimination - A Study on the Life Satisfaction of Turkish and Moroccan Minorities in the Netherlands - Arat, Ece; Bilgili, Özge (Frontiers in Sociology, 2021)
Perceived ethnic discrimination is known to decrease minorities’ life satisfaction. This research investigates the extent to which minorities’ local and transnational co-ethnic social ties mitigate the negative effects of perceived discrimination on life satisfaction. Put differently, focusing on the experiences of Turkish and Moroccan minorities, we discuss whether co-ethnic social ties, both locally and transnationally embedded, can be considered as coping mechanisms against perceived discrimination. Furthermore, we investigate whether these mechanisms work differently for first- and second-generation minorities. Using Netherlands Longitudinal Life-course Study, we reveal that perceived discrimination is positively associated with local co-ethnic social ties in Netherlands which consequently predicts higher life satisfaction for both generations. Surprisingly, we also show that only among the second generation perceived discrimination is associated with stronger transnational co-ethnic social ties, but not the first generation. Having these transnational ties however are beneficial for life satisfaction of both generations. Consequently, we highlight the importance of recognizing transnational embeddedness of minorities and studying the effects transnational co-ethnic social ties on subjective well-being outcomes especially for second-generation minorities.